2020
DOI: 10.1061/(asce)st.1943-541x.0002710
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steel Reinforcement on the Performance of Elastomeric Bearings

Abstract: Seismic isolation is an effective measure for mitigating the earthquake hazard on important structures such as hospitals, bridges, and nuclear power plants. Seismically isolated structures should remain essentially elastic for the design earthquake, experiencing minimal or no damage. Steel-reinforced elastomeric bearings are seismic isolation devices that are used extensively for the protection of bridges. Because isolators are critical elements of an isolated bridge, they should experience limited, if any, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The steel shims constrain the global lateral bulging of the rubber to guarantee a certain vertical stiffness of the bearing. [ 41 ] The vertical stiffness of an elastomeric isolator depends on the instantaneous compression modulus E c of an elastomer layer which has both sides provided with plates. E c is estimated using the relationship proposed by [ 34,42 ] Enormalc=E0false(1 +2kSfalse)where E 0 is the compression modulus for unconfined rubber in a test machine for the stain of a few percent.…”
Section: Instantaneous Compression Modulusmentioning
confidence: 99%
“…The steel shims constrain the global lateral bulging of the rubber to guarantee a certain vertical stiffness of the bearing. [ 41 ] The vertical stiffness of an elastomeric isolator depends on the instantaneous compression modulus E c of an elastomer layer which has both sides provided with plates. E c is estimated using the relationship proposed by [ 34,42 ] Enormalc=E0false(1 +2kSfalse)where E 0 is the compression modulus for unconfined rubber in a test machine for the stain of a few percent.…”
Section: Instantaneous Compression Modulusmentioning
confidence: 99%
“…e characteristics, such as bearings constructability, availability, and technique, are also very important to build a bridge, but the safety of the bridge, especially seismic performance, was studied in this paper [49]. erefore, the No.…”
Section: Case Setting Of Bearingsmentioning
confidence: 99%
“…e limitations of the investigations lie in the inability to address the details of the mechanical behaviours of interlaminated rubber layers [4], and the traditional approach cannot handle the influence of geometric and material parameters of each rubber layer. In addition, according to the results of finite element analysis, Kalfas et al [11,12] found the damage magnitude of each rubber layer and steel shim is different after the bearing under a certain load. When Haringx's theory is applied to the damage identification of laminated rubber bearings, the damage of certain layers cannot be located; consequently, the early minor damage in the bearings is difficult to identify.…”
Section: Introductionmentioning
confidence: 99%